Why are European IPOs so rarely priced outside the indicative price range? - Jenkinson, Tim; Morrison, Alan D.; Wilhelm, William J. (Journal of Financial Economics, 2006)
Unlike in the U.S., the initial price range for European IPOs is seldom revised, although issues are often priced at the upper bound. We develop a model that explains this seemingly inefficient pricing behavior. As in Europe, but not in the U.S., underwriters in the model obtain information from investors before establishing the indicative price range. A commitment to stay within the range is necessary to extract private information from investors. Ours is therefore the first treatment in which the bookbuilding range has a clear economic role. The model has important implications for empirical research based on European primary market data.